2023
DOI: 10.1177/00368504221149797
|View full text |Cite
|
Sign up to set email alerts
|

Thermal efficiency of radiated tetra-hybrid nanofluid [(Al2O3-CuO-TiO2-Ag)/water]tetra under permeability effects over vertically aligned cylinder subject to magnetic field and combined convection

Abstract: Applications The nanofluids and their upgraded version (ternary and tetra nanofluids) have a very rich thermal mechanism and convinced engineers and industrialist because of their dominant characteristics. These broadly use in chemical, applied thermal, mechanical engineering, and biotechnology. Particularly, heat transfer over a cylindrical surface is important in automobiles and heavy machinery. Purpose and Methodology Keeping in front the heat transfer applications, a model for Tetra-Composite Nanofluid [(A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The nanofluid model that evolved in this study for tetra hybrid nanofluid [40,41] are given in Table 1.…”
Section: Newly Developed Tetra Nanofluid Modelsmentioning
confidence: 99%
“…The nanofluid model that evolved in this study for tetra hybrid nanofluid [40,41] are given in Table 1.…”
Section: Newly Developed Tetra Nanofluid Modelsmentioning
confidence: 99%
“…Some other studies also explains effect of thermal radiation are. [27][28][29] In order to provide insight on the underlying principles of triple diffusive flows and its implications for applications in a variety of domains, including materials science and oceanography, our research aims to untangle the complex dynamics of these flows. Along, looking at the previously mentioned literature, it appears that, as far as we are aware, no research has been published that explains the mass transfer, flow, and heat properties of the nonlinear radiative heat flux in triple diffusive convection with convective boundary conditions of nano fluid with hall current effect, joule heating and mass flux condition.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Indumathi et al examined a hybrid nanofluid with a permeable surface under the suction and injection process. The results of the physical model showed that increasing the number of nanoparticles in the basic fluid will result in a decrease in the velocity of hybrid nanofluids. In 2022, Mburu et al investigated the unsteady, two-dimensional, viscous, and incompressible flow of the boundary layer of an electrically conducting nanofluid through porous plates. Bivariate spectral quasilinearization (BSQL) was used for the model study.…”
Section: Introductionmentioning
confidence: 99%